2012
DOI: 10.1371/journal.pone.0049364
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Comet-FISH Assay to Compare DNA Damage and Repair in p53 and hTERT Genes following Ionizing Radiation

Abstract: The alkaline single cell gel electrophoresis (comet) assay can be combined with fluorescent in situ hybridisation (FISH) methodology in order to investigate the localisation of specific gene domains within an individual cell. The number and position of the fluorescent signal(s) provides information about the relative damage and subsequent repair that is occurring in the targeted gene domain(s). In this study, we have optimised the comet-FISH assay to detect and compare DNA damage and repair in the p53 and hTER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Simultaneously, they also established that Per1 directly acts on the p53 node, as checkpoint components upstream of p53 remained active in response to DNA damage. Quantitative transcriptional analyses of p53 target genes demonstrated that unbound p53 was absolutely required for the activation of the DNA-damage response (Dakup et al, 2016;McKenna et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…Simultaneously, they also established that Per1 directly acts on the p53 node, as checkpoint components upstream of p53 remained active in response to DNA damage. Quantitative transcriptional analyses of p53 target genes demonstrated that unbound p53 was absolutely required for the activation of the DNA-damage response (Dakup et al, 2016;McKenna et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…Moreover, C-MYC is also controlled by the circadian clock [30]; together with the two proteins described above, it can induce the apoptosis of U343 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates the utility of the comet-FISH to analyse the fragmentation of NORs on hemocytes of Crassostrea gigas and reveals its potential use to analyse damaged induced by genotoxicant exposure in specific genes. However, despite of its efficacy in the assignment of DNA damage to genes and specific chromosomal regions (Mladinic et al, 2012;Reiter et al, 2012;Volpato et al, 2008, Hovhannisyan et al, 2005 and in the analysis of cellular DNA repair capacity (Guo et al, 2013;McKenna et al, 2012), this technique has not been widely employed in the field of ecotoxicology. This can be explained by the fact that its application, optimization and interpretation of the results require experience in gene mapping by FISH.…”
Section: Discussionmentioning
confidence: 99%